Analisis Penerapan Metode Perhitungan Penyusutan Aset Tetap Berdasarkan Standar Akuntansi Keuangan dan Pengaruhnya terhadap Penyajian Laporan Keuangan pada PT. X di Surabaya - Mahira Nur Alfiani; Tjandra Wasesa; Heri Toni P; Wiratna Wiratna; Diana Zuhroh (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
This research is a qualitative study that utilizes both primary and secondary data sources conducted at PT. X in Surabaya, a company engaged in land transportation for cargo delivery or expedition purposes. The study aims to examine the implementation of fixed asset depreciation methods and their impact on financial reporting at PT. X in Surabaya. The findings reveal that the company does not include all related costs in determining the acquisition cost of its fixed assets, and the determination of the depreciation calculation period for fixed assets is not based on Ministry of Finance regulations, thus the company has not applied them in accordance with applicable financial accounting standards.